Obtenção de bioherbicida a partir de fungo isolado do bioma Mata Atlântica - Bastos, Juliana de Oliveira (2016)
The search for decreases in losses of agricultural production makes it necessary to use pesticides to combat pests and weeds. The use of products derived from the chemical industry on disease control in agriculture has been questioned because of its adverses effects. As a result, many synthetic agricultural products were removed from markets, which creates the need for development of alternative means of weed management. There is an interest in the discovery and development of new bioherbicides from micro-organisms, especially fungi, and it’s an important tool in biological control. Therefore, the aim of this work was to produce a bioherbicide from submerged fermentation of the fungus Fusarium graminearum isolated from the Atlantic Forest biome and evaluate its phytotoxic potential. Initially a experimental design Plackett Burman type was applied, and the variables measured in biomass yield were pH (5-7), glucose (5-15 g.L-1), peptone (5-15 g.L-1) and yeast extract (5-10 g.L-1). Only peptone had a significant positive effect on biomass yield, so new tests with different concentrations of peptone (10-80 g.L-1) were conducted. and post-emergence test was applied with Cucumis sativus . var. wisconsin plants (cucumber) after 21 days. At the first post-emergence evaluation for the phytotoxicity parameter the best results occurred at a concentration of 40 g.L-1 peptone. In this condition, two treatments, partial lyophilization and membrane separation were used for concentration of the broth. In the evaluation of phytopathogen action after application of the treated supernatant was observed reduction of 100% of the length of the roots, reduced shoot growth and visually greater phytotoxicity in treatment using the permeated fraction of the membrane separation process. Among the compounds identified through gas chromatography, there was the presence of nitrogenous heterocyclic, including: pyrimidines, piperazines, pyrrolidines, piperidines, aziridines, quinolines and tetrazoles, but other studies are needed to define which one (s) toxin (s) are causing the phytotoxic effect.